Effect of a pelvic belt on EMG activity during manual load lifting - Marcelo Pinto Pereira; Mauro Gonçalves (Universidade Federal de Santa Catarina, 2009)
Manual lifting (ML) capacity is still a matter of concern for industry administrators and electromyography (EMG) seems to be a good alternative for the evaluation of muscles involved in this task. However, the reliability of these measures is very important. Thus, the objective of this study was to evaluate the influence of a pelvic belt on EMG activity of the erector spinus (ES) and rectus femoralis (RF) muscles during ML and during maximal voluntary contractions (MVC) of trunk extension performed before (baseline) and after ML. In addition, the variabilityin the EMG signal normalized by the following three different methods was evaluated: peak EMG activity, mean EMG activity, and EMG activity obtained during MVC. Eight volunteers performed ML of 15% and 25% of their body weight for 1 minute in the presence or absence of a pelvic belt. The coefficient of variation (CV) of the EMG signal obtained for the ES and RF muscles was calculated during ML. Load cell traction values and the electromyographic variables RMS, median frequency, mean power frequency and total power of the ES muscle were obtained during MVC. The results showed lower CV (smaller variability) when the EMG signal was normalized by peak activity, with this method thus being preferable. During MVC, only the load cell traction value differed from baseline after ML of 25% body weight without the pelvic belt (p=0.035), a finding suggesting rapid recovery of ES muscle after ML for 1 minute.